Factors predicting protracted improvement after pallidal DBS for primary dystonia: the role of age and disease duration - Isaias, Ioannis U.; Volkmann, Jens; Kupsch, Andreas; Burgunder, Jean-Marc; Ostrem, Jill L.; Alterman, Ron L.; Mehdorn, Hubertus Maximilian; Schönecker, Thomas; Krauss, Joachim K.; Starr, Philip; Reese, Rene; Kühn, Andrea A.; et al. (Journal of neurology, 2011)
In many patients, optimal results after pallidal deep brain stimulation (DBS) for primary dystonia may appear over several months, possibly beyond 1 year after implant. In order to elucidate the factors predicting such protracted clinical effect, we retrospectively reviewed the clinical records of 44 patients with primary dystonia and bilateral pallidal DBS implants. Patients with fixed skeletal deformities, as well as those with a history of prior ablative procedures, were excluded. The Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) scores at baseline, 1 and 3 years after DBS were used to evaluate clinical outcome. All subjects showed a significant improvement after DBS implants (mean BFMDRS improvement of 74.9% at 1 year and 82.6% at 3 years). Disease duration (DD, median 15 years, range 2–42) and age at surgery (AS, median 31 years, range 10–59) showed a significant negative correlation with DBS outcome at 1 and 3 years. A partition analysis, using DD and AS, clustered subjects into three groups: (1) younger subjects with shorter DD ( n = 19, AS < 27, DD ≤ 17); (2) older subjects with shorter DD ( n = 8, DD ≤ 17, AS ≥ 27); (3) older subjects with longer DD ( n = 17, DD > 17, AS ≥ 27). Younger patients with short DD benefitted more and faster than older patients, who however continued to improve 10% on average 1 year after DBS implants. Our data suggest that subjects with short DD may expect to achieve a better general outcome than those with longer DD and that AS may influence the time necessary to achieve maximal clinical response.